RANCANG BANGUN ALAT PENGUKUR DAN PENGATUR SUHU RUANGAN GREENHOUSE TANAMAN MELON HIDROPONIK BERBASIS IOT - Adam Kurniawan; M. Dewi Manikta Puspitasari; Miftakhul Maulidina; Elsanda Merita Indrawati (Universitas Nusantara PGRI Kediri, 2026)
Agriculture has experienced developments, especially in the horticultural sector that has high economic value, such as the melon business cultivated through Greenhouses, but the indoor temperature is higher than outside due to the greenhouse effect and the absence of a temperature control system in the Greenhouse. The purpose of this study is to determine the design and working system of a hydroponic melon temperature measuring and regulating device in an IoT-based Greenhouse in stabilizing the temperature. The research model used is a